Religiosity/Spirituality and Mental Health and Quality of Life of Early Pregnant Women - Piccinini, Clarissa Rocha Panconi (Journal of religion and health, 2021)
The present study aims to investigate how religious/spiritual (R/S) beliefs are associated with depressive, anxious and stress symptoms and quality of life (QOL) of 160 Brazilian women in early pregnancy. In this cross-sectional study, religiosity/spirituality (DUREL, Daily Spiritual Experiences, Brief-RCOPE), mental health (DASS-21) and quality of life (WHOQOL-Bref) were assessed. Negative R/S coping was associated with higher levels of depressive, anxious and stress symptoms and worse physical and psychological QOL. On the other hand, positive R/S coping, intrinsic religiosity, and spirituality were associated with better psychological QOL, while only spirituality was associated with better social QOL.